PENERAPAN METODE COLLISION DETECTION PADA GAME BERHITUNG UNTUK ANAK USIA TK - Rahma, Salsabella; Ardhianto, Eka (Information Technology and Telematics, 2018)
ABSTRACT The current technological development intensified, particularly in the technology game.In addition to means of entertainment games also serve as a medium of instruction. The game is the thing that can not be separated from the development of a child.This counting game implements the basic count of operations such as addition and subtraction.So the kids who play this game are expected to hone the ability to count quickly.Therefore the author wanted to make the game counting methods use collision detection. A method of collision detection, starting from the analysis of design, manufacture, testing and maintaenance. The game is a matter of calculation in the form of addition and subtraction, and ball game pantul. The making of the application using the counstruct 2. The final result of the development of the system is a game application that presents a counting game that is not only fun and entertaining, but also train the ability and memory players in counting.